Microstructure Evolution in Mg-Zn-Zr-Gd Biodegradable Alloy: The Decisive Bridge Between Extrusion Temperature and Performance - Yao, Huai; Wen, Jiu-Ba; Xiong, Yi; Lu, Yan; Huttula, Marko (Frontiers in Chemistry, 2018)
Being a biocompatible metal with similar mechanical properties as bones, magnesium bears both biodegradability suitable for bone substitution and chemical reactivity detrimental in bio-ambiences. To benefit its biomaterial applications, we developed Mg-2.0Zn-0.5Zr-3.0Gd (wt%) alloy through hot extrusion and tailored its biodegradability by just varying the extrusion temperatures during alloy preparations. The as-cast alloy is composed of the α-Mg matrix, a network of the fish-bone shaped and ellipsoidal (Mg, Zn)3Gd phase, and a lamellar long period stacking ordered phase. Surface content of dynamically recrystallized (DRXed) and large deformed grains increases within 330-350 C of the extrusion temperature, and decreases within 350-370 C. Sample second phase contains the (Mg, Zn)3Gd nano-rods parallel to the extrusion direction, and Mg2Zn11 nanoprecipitation when temperature tuned above 350 C. Refining microstructures leads to different anticorrosive ability of the alloys as given by immersion and electrochemical corrosion tests in the simulated body fluids. The sample extruded at 350 C owns the best anticorrosive ability thanks to structural impacts where large DRXed portions and uniform nanosized grains reduce chemical potentials among composites, and passivate the extruded surfaces. Besides materials applications, the in vitro mechanism revealed here is hoped to inspire similar researches in biometal developments.